Dissemination of Economic Resilience in Scientific Evolution to Strengthen Community Economy in Facing Covid-19 Pandemic Through Bibliometric Analysis - Sarjana, Sri; Najib, Mahsa Amira Anindya; Khayati, Nur (Journal of Developing Economies, 2022)
Economic resilience is the financial ability of a nation that relies on the utilization of existing resources in dealing with various problems whose sources are internal or external to create community welfare. Economic resilience is currently experiencing a severe test for all countries due to covid-19 pandemic, which has an impact on the economic crisis. A qualitative approach is applied by actualizing bibliometric analysis of the concept of economic resilience, which is the main focus. The research data is sourced from scientific journals on the concept of economic resilience, which was explored during the time span of the pandemic. The results of the study state that several theories found have a novel value that is rarely published and can help accelerate economic resilience, including disaster risk reduction, independent village, global value chain, ecology resilience, global recession, banking crisis, regional resilience, and village government. The main clusters derived from economic resilience include economic recovery, economic crisis, adaptation strategy, community empowerment, economic vulnerability, financial inclusion, circular economy, and good governance. Knowledge development needs to be carried out to disseminate current theories and issues so that researchers or academics can study and explore more so that the derived knowledge can help provide solutions and improve economic conditions.